2021
DOI: 10.1016/j.micpath.2021.105151
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ CD8αα+ T cells in the gastric epithelium mediate chronic inflammation induced by Helicobacter felis

Abstract: CD4+ CD8αα+ double-positive intraepithelial T lymphocytes (DP T cells), a newly characterized subset of intraepithelial T cell, has been reported to contribute to local immunosuppression. However, whether DP T cells are present in Helicobacter. pylori-induced gastritis, and their relationship with disease prognosis remain to be elucidated. In this study, We established chronic gastritis models through Helicobacter felis (H. felis) infection. Gastric in ltrating lymphocytes were isolated from H. felis-induced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…al. demonstrated that CD4+ CD8αα+ double-positive intraepithelial T lymphocytes (DP T cells) play an immunosuppressive role in H. felis -induced gastritis, mediating chronic inflammation and possibly affecting disease prognosis [ 145 ]. Furthermore, a recent study has implicated the role of APRIL (a proliferation inducing ligand) in the development of gastric MALT lymphoma [ 146 ].…”
Section: Animal Models To Evaluate the Role Of Host Factors In Pathog...mentioning
confidence: 99%
“…al. demonstrated that CD4+ CD8αα+ double-positive intraepithelial T lymphocytes (DP T cells) play an immunosuppressive role in H. felis -induced gastritis, mediating chronic inflammation and possibly affecting disease prognosis [ 145 ]. Furthermore, a recent study has implicated the role of APRIL (a proliferation inducing ligand) in the development of gastric MALT lymphoma [ 146 ].…”
Section: Animal Models To Evaluate the Role Of Host Factors In Pathog...mentioning
confidence: 99%